SPECIES OF SILESIS CANDEZE FROM NORTH INDIA (COLEOPTERA : ELATERIDAE) - VATS, L.K.; CHAUHAN, R.L. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1993)
Five species of Silesis Candeze, namely, S. protuberancis sp. nov., S. almorensis sp. nov., S. nigrostriatus sp. nov, S. portulacis sp. nov. and S. simulatus Candeze have been described in detail. These species are confined to the hill region of Northern India. The distinctive characters are the comparative length of second and third antennal segments; dimensions of prothorax and length of its carinae, anterior margin of scutellum and colour of elytra. Aedeagus is longer than parameres and the latter may or may not bear the subapical processes.